Association between waist circumference and gray matter volume in 2344 individuals from two adult community-based samples - Janowitz, Deborah; Wittfeld, Katharina; Terock, Jan; Freyberger, Harald Jürgen; Hegenscheid, Katrin; Völzke, Henry; Habes, Mohamad; Hosten, Norbert; Friedrich, Nele; Nauck, Matthias; Domanska, Grazyna; Grabe, Hans Jörgen (NeuroImage (Orlando, Fla.), 2015)
We analyzed the putative association between abdominal obesity (measured in waist circumference) and gray matter volume (Study of Health in Pomerania: SHIP-2, N=758) adjusted for age and gender by applying volumetric analysis and voxel-based morphometry (VBM) with VBM8 to brain magnetic resonance (MR) imaging. We sought replication in a second, independent population sample (SHIP-TREND, N=1586). In a combined analysis (SHIP-2 and SHIP-TREND) we investigated the impact of hypertension, type II diabetes and blood lipids on the association between waist circumference and gray matter. Volumetric analysis revealed a significant inverse association between waist circumference and gray matter volume. VBM in SHIP-2 indicated distinct inverse associations in the following structures for both hemispheres: frontal lobe, temporal lobes, pre- and postcentral gyrus, supplementary motor area, supramarginal gyrus, insula, cingulate gyrus, caudate nucleus, olfactory sulcus, para-/hippocampus, gyrus rectus, amygdala, globus pallidus, putamen, cerebellum, fusiform and lingual gyrus, (pre-) cuneus and thalamus. These areas were replicated in SHIP-TREND. More than 76% of the voxels with significant gray matter volume reduction in SHIP-2 were also distinct in TREND. These brain areas are involved in cognition, attention to interoceptive signals as satiety or reward and control food intake. Due to our cross-sectional design we cannot clarify the causal direction of the association. However, previous studies described an association between subjects with higher waist circumference and future cognitive decline suggesting a progressive brain alteration in obese subjects. Pathomechanisms may involve chronic inflammation, increased oxidative stress or cellular autophagy associated with obesity. •Highly significant associations between abdominal obesity and reduced gray matter volume•76% of the areas with gray matter volume differences were replicated in an independent sample.•Adjustment for metabolic factors did not change results.